Public Financing of Research Projects in Poland — Its Image and Consequences? - Feldy Marzena (Marketing of Scientific and Research Organizations, 2016)
Both the size of appropriation as well as their distribution have had a profound impact on the shape and activities of the science sector. The creation of a fair system of distribution of public resources to research that will also facilitate the effective implementation of the pursued scientific policy goals represents a major challenge. The issue of the determination of the right proportions of individual distribution channels remains critical. Despite this task being the responsibility of the State, establishing cooperation in this respect with the scientific community is desirable. The implementation of solutions that raise the concerns of scientists leads to system instability and reduced effectiveness which is manifest among others in a lower level of indicators of scientific excellence and innovation in the country.